Imposex in Canarium Urceus collected from the seashore within the vicinity of the port area in Oroquieta City, Misamis Occidental - Maata, Kayzel J.; Silapan, Judith R. (Cebu City, Cebu Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Antifouling paints are used to address the biofouling problem encountered by marine vessels. Since the 1960s, the biocide tributyltin (TBT) has been widely used in antifouling paints but was banned worldwide in 2008 because it has been demonstrated to have a negative impact on a range of marine species. An indicator of TBT contamination is imposex, a condition in which male sex organs develop in female gastropods, since it has been found to have a significant correlation with proximity to harbors and marinas. While imposex has been extensively studied in other parts of the world, published studies in the Philippines remain limited. The coastal area of Oroquieta, Misamis Occidental, starting from Oroquieta Fish Port, was assessed for imposex incidence. A total of 120 Canarium urceus samples were collected and three indices were calculated to estimate the occurrence of imposex. The incidence of imposex (I%) was highest at the sampling site nearest to the port and decreased towards the sampling site farthest from the port. Similarly, the Conversion of Potential Female to Imposex Index (CPFII) followed the same trend, indicating that the probability of normal females developing imposex is also highest in the first sampling site and decreases with increasing distance from the port. The Relative Penis Size Index (RPSI) did not follow the same trend as the other two indices because it was the second sampling site that had a higher index. This suggests that the samples collected at the sampling site nearest to the fishing port may have had deformed penises, which is indicative of severe TBT contamination. Furthermore, the gonads of imposex females exhibited the presence of ovarian spermatogenesis. The detection of imposex in the sampling sites suggests that TBT pollution could still be present in the port area of Oroquieta City.
Thesis (Bachelor of Science in Biology). University of the Philippines Cebu. June 2022